Reinforced concrete - Holland, R. (Appraisal and repair of building structures., 1997)
This title provides guidance on appraisal and repair of reinforced concrete building structures. It addresses the problems related to reinforced concrete, corrosion of reinforcement, cracking, cathodic protection and protective coatings, and it highlights the advantages and/or problems of each while explaining the methods and options available.